Peningkatan Efisiensi dan Tekno-Ekonomi Produksi Purus Kayu Menggunakan Inovasi Mesin Purus Kayu Terintegrasi - Barokah, Ramanda Ridho; Wijayanto, Danar Susilo (FKIP Universitas Sebelas Maret, 2025)
Wooden tenons are crucial components in joinery used in furniture manufacturing. Unfortunately, their production still heavily relies on manual methods, leading to inefficiencies. This research focuses on developing and evaluating an integrated wooden tenon machine to enhance efficiency and productivity in furniture manufacturing. Through quantitative experimental methods, the study compares the speed and capacity of wooden tenon production between manual methods and the integrated machine. Techno-economic analysis is also conducted to assess production feasibility. Experiments take place at UD. Sunarso Mebel using Suren (Toona Sureni) wood with five different size specifications: 3 cm thick, 40 cm long, and varying widths of 6 cm, 9 cm, 12 cm, 14 cm, and 25 cm. Results indicate that the integrated machine boosts wooden tenon production speed by up to 10 times and capacity by up to 9 times compared to manual methods. Additionally, the quality of dowels produced by the machine is superior due to smoother and more precise surfaces. With low production and operational costs, the machine is economically recommended for profit enhancement. The investment in the integrated wooden tenon machine can be recouped within just one month.